MICROBIOLOGICAL ASPECT OF ECOLOGICAL BIOTECHNOLOGY OF APPLYING “RADOROD” BIOLOGICAL PREPARATION IN THE AGRARIAN SPHERE - Pasenko, A. V.; Dihtyar, S. V.; Sakun, O. A.; Nykyforova, O. O.; Tsymbal, I. I. (Scientific Progress & Innovations, 2021)
In agro-technologies, a promising way to increase soil fertility and intensify plant production is the use of certain biochemically active strains of microorganisms that provide humification of the organic component of plant residues in situ. There is a line of “Radorod” bio-fertilizers, different modifications of the fertilizer are used depending on agro conditions and the grown crop. The paper investigates the effectiveness of ap-plying “Radorod PZ” biological preparation, which contains microorganisms-destructors accelerating the mineralization of complex organic compounds and, thus, increasing soil fertility. Soil samples were taken for the bio-fertilizer treatment: common chernozem (black soil) and podzolized (bleached) chernozem. The study of soil micro-biocenosis after treatment with “Radorod PZ” preparation was carried out by studying the micro-landscapes of soil samples using the method of fouling glasses by M. G. Kholodny. The study of the total number of aerobic mesophiles and colonies’ culture characteristics of microorganisms of the microbial cenosis of the studied soil samples was conducted after sowing microbiota on the nutrient medium of MPA by microscopic examination. The dominant group of microorganisms of Actinobacteria class in the mixed culture of the soil microbiota after applying “Radorod PZ” was determined by culture characteristics. In case of adding the biological preparation to the common chernozem, there was an increase in the percentage of Actinobacteria class representatives from the total amount of soil microbiota by 14 %, and when adding to podsolized chernozem – by 4 %. The difference in the content of microorganisms in soils of different gene-sis is explained by the dominance of Actinobacteria in environments enriched with plant residues. Podzolized hernozem is poor in humic substances, so the development of actinomycetes is somewhat slowed down. Ac-tinobacteria have a powerful enzyme complex, and they are active bio-destructors. It is recommended to use “Radorod PZ” bio-preparation to increase soil biological activity. The use of “Radorod PZ” bio-preparation to accelerate the process of mineralization of organic waste from agricultural production – plant residues in the field in situ is promising. The paper substantiates the application of “Radorod PZ” as a bio-agent of ecological biotechnology to restore soil fertility, increase crop growing productivity and maintain the environmental balance of agro-ecosystems.